A new species of the Genus Boysidia (Pulmonata: Pupillidae) from Northern Thailand - P. Dumrongrojwattana; S. Assawawattagee (Penerbit Universiti Kebangsaan Malaysia, 2018)
A new species of the genus Boysidia Ancey, 1881, collected from Doi Pha Tang, Chiangrai Province, Northern Thailand, is described as B. phatangensis sp. nov. The new species is characterized by its small size, conical shape with 5¼ - 5½ whorls, yellowish-brown color, aperture subquadrate consists of 6 barrier teeth, outer lip expanded. B. phatangensis seem limited to the high altitude area in northern part of Thailand.